Effect of microwave sintering on the properties of copper oxide doped alumina toughened zirconia (ATZ) - Abbas M.K.G.; Ramesh S.; Tasfy S.F.H.; Lee K.Y.S. (Elsevier Editora Ltda, 2024)
This study investigated the effect of copper oxide addition on the alumina toughened zirconia composite ceramic using microwave sintering. CuO amounts (0.051 wt%) were examined at sintering temperatures (12501500 C). Investigations covered hardness, toughness, phase stability, microstructure, and densification. Optimum doping was 0.2 wt%, resulting in a composite with 99% relative density at 1500 C, Vickers hardness of 13.1 GPa, and fracture toughness of 7.1 MPa m1/2. Low-temperature degradation showed disrupted phase stability above 1400 C, with CuO unable to prevent ageing-induced phase transformation. 2023 The Author(s)